Robustness Report on "Innovation and Institutional Ownership", by Aghion, Philippe, John van Reenen, and Luigi Zingales (2013) - Douglas Campbell; Abel Brodeur; Magnus Johannesson; Joseph Kopecky; Lester Lusher; Nikita Tsoy (Institute for Replication (I4R), 2024)
Aghion, Van Reenen and Zingales (2013) find that institutional ownership causes an increase in innovation as measured by citation-weighted patent counts. To identify a causal effect, they use membership in the S&P 500 as an instrument for institutional ownership in a panel regression. We first replicate all regression tables in Aghion et al., and then test for robustness, mainly by adding in firm and sector*year fixed effects. We find that the positive relationship between institutional ownership and innovation is robust in 22% of robustness checks. On average, 2nd stage z-scores were just 42.7% of the original study. We find that when we include firm fixed effects, membership in the S&P 500 actually has a negative (though significant only at the 10% level) impact on institutional ownership (among non-indexed funds). Lastly, we find that the original control-function IV regression suffers from multi-collinearity, complicating inference.
Keywords: G23; G32; L25; M10; O31; O34; 330; Innovation; Patents; Institutional Investment